A New Technique for Simple Renal Cyst: Cystoretroperitoneal Shunt - Onder Canguven; Cemal Goktas; Faruk Yencilek; Cihangir Cetinel; Selami Albayrak (Advances in Urology)
Purpose. To evaluate the results of patient symptoms and radiologic outcomes of cystoretroperitoneal shunt (CRS) technique in the treatment of symptomatic simple renal cysts. Patients and Methods. In a prospective study, 37 patients with a simple renal cyst were treated with ultrasound-guided percutaneous CRS-catheter. Radiological success was indicated as no recurrence of the cyst or a reduction in cyst volume by at least half. Results. CRS technique was performed successfully in 36 patients with a simple renal cyst. The mean size of all cysts decreased from 8.8 cm (range 7 to 14) to 1.7 cm (range 0 to 9; 𝑃<.001). Symptomatic success (pain relief) was achieved in 29/36 (80.5%) of patients, and radiographic success was achieved in 23/36 (63.8%) of patients, with a median follow-up of 16 months (range 6 to 24). Conclusion. Ultrasound-guided percutaneous CRS technique for simple renal cysts is fast, safe, effective, and inexpensive.